Infestasi Caplak Ixodidae pada Sapi Lokal di Kelurahan Balai Gadang Kecamatan Koto Tangah Kota Padang - Aulia Dina Kristina; Agus Setiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Abdi Nusantara XIII is a facility for students of the Faculty of Veterinary Medicine IPB University as part of social change agents to realize the third Tri Dharma of Higher Education, namely the Community Service Dharma. One of the activities of Abdi Nusantara XIII have been held using the method of observation and active participation in 18 July 2019 with Puskeswan Air Pacah under the Department of Agriculture of Padang City and students of Abdi Nusantara XIII FKH IPB. The purpose of this activity is to maintain the health of livestock residents through animal health services conducted routinely by the local service. As many as 16 local cows received health services. The observations showed that the prevalence of hard tick infestation in local cow in one of the Balai Gadang Village farmers reached 100%. Ticks are obligate bloodsucking ectoparasites in vertebrates, especially mammals, birds and reptiles throughout the world. Reportedly consists of two families of ticks, namely Ixodidae (hard tick) and Argasidae (soft tick). Found three genera of hard ticks have been identified namely; the genus Boophilus is the tick most commonly followed by Rhipicephalus and Ambylomma. This study shows that there is an abundance of high tick populations in livestock areas. Thus, it is highly recommended to carry out a tick control strategy, the application of akarisida to reduce the tick population and to improve good enclosure management to overcome the tick problem. Keywords: abdi nusantara XIII, ambylomma, boophilus, rhipicephalus, Padang local cow